Upaya Guru PAI dalam Mengatasi Tantangan Generasi Z pada Pembelajaran Pendidikan Agama Islam di SMAN 2 Kota Pasuruan - Akhadiyah, Mariyatul; Ma’ruf, M.; Nurhasan, Nurhasan (Tarbiyatuna Kajian Pendidikan Islam, 2026)
This study examines the strategies of Islamic Religious Education (PAI) teachers in addressing the learning challenges posed by the characteristics of Generation Z at SMAN 2 Pasuruan City. Generation Z is known to be very familiar with technology, has a fast learning style, and prefers practical and enjoyable learning methods, while PAI material demands a deep understanding of religious values. This study used a case study approach, data collection techniques including interviews, observation, and documentation. The research subjects consisted of PAI teachers and grades 10 and 11 students. Data were analyzed through a process of data reduction, presentation, and conclusion drawing. The results showed that teachers implemented strategies such as a personal and empathetic approach, active and innovative learning, the use of digital media, and linking the material to everyday life. The main challenges faced included students' easily bored and critical nature, low participation in active strategies, internet access constraints, and limited learning time during the day. To overcome these challenges, teachers prioritized more creative communication and provided role models in religious values. These findings indicate that adapting learning strategies to the characteristics of Generation Z is crucial for improving the effectiveness of PAI learning.